2019
DOI: 10.1017/jfm.2019.671
|View full text |Cite
|
Sign up to set email alerts
|

Shoaling mode-2 internal solitary-like waves

Abstract: The propagation of a train of mode-2 internal solitary-like waves (ISWs) over a uniformly sloping, solid topographic boundary, has been studied by means of a combined laboratory and numerical investigation. The waves are generated by a lock-release method. Features of their shoaling include (i) formation of an oscillatory tail, (ii) degeneration of the wave form, (iii) wave run up, (iv) boundary layer separation, (v) vortex formation and re-suspension at the bed and (vi) a reflected wave signal. Slope steepnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 62 publications
5
21
0
Order By: Relevance
“…6(i)]. A similar shoaling process for second-mode solitary waves has been recently reported in laboratory and numerical experiments by Carr et al [31], who found that the wave disintegration resembles the fission process characterized by Aghsaee et al [52] and Arthur and Fringer [54]. In our experiments, however, the shoaling processes occur periodically.…”
Section: Shoaling Processsupporting
confidence: 90%
See 4 more Smart Citations
“…6(i)]. A similar shoaling process for second-mode solitary waves has been recently reported in laboratory and numerical experiments by Carr et al [31], who found that the wave disintegration resembles the fission process characterized by Aghsaee et al [52] and Arthur and Fringer [54]. In our experiments, however, the shoaling processes occur periodically.…”
Section: Shoaling Processsupporting
confidence: 90%
“…Although the mechanisms leading to the second-mode solitarylike waves differ, in both studies, the nonlinear internal waves have similar degeneration processes as they approach the sloping boundary. However, for the same bottom slope, s ≈ 3%, the second-mode nonlinear internal waves (in case 3) present a robust wave reflection, while the similar internal solitarylike waves in Carr et al [31] show no wave reflection. This last result suggests that the wind-driven baroclinic circulation might be crucial for supporting the periodic propagation of the nonlinear internal waves from side to side in the stratified basin.…”
Section: Discussion and Summarymentioning
confidence: 79%
See 3 more Smart Citations